Is it possible to standardize the treatment of primary spontaneous pneumothorax? Part 1: etiology, symptoms, diagnostics, minimally invasive treatment - Rokicki, Wojciech; Rokicki, Marek; Wojtacha, Jacek; Filipowski, Marek; Dżejlili, Agata; Czyżewski, Damian (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2016)
The authors of this report present the history of primary spontaneous pneumothorax (PSP) treatment, its etiology, clinical symptoms, and diagnostic methodology. Further, they discuss minimally invasive methods of treating PSP such as thoracentesis and chemical pleurodesis. They discuss the pros and cons of each method, emphasizing that, according to the international recommendations, they should be used as the first line of treatment for PSP.